Diaspora for development in Africa - Plaza, Sonia (Washington, D.C World Bank, 2011)
MIGRATION PRESENTS SIGNIFICANT untapped potential for development. The diaspora of developing countries can be a potent force for development through remittances, but also through the promotion of trade, investment, and knowledge and technology transfers.
Includes bibliographical references and index.
Keywords: Migration for Development in Africa (Program)